Community health worker-delivered counselling for common mental disorders among chronic disease patients in South Africa: a feasibility study. Issue 1 (15th January 2019) - Myers, Bronwyn; Petersen-Williams, Petal; van der Westhuizen, Claire; Lund, Crick; Lombard, Carl; Joska, John A; Levitt, Naomi S; Butler, Christopher; Naledi, Tracey; Milligan, Peter; Stein, Dan J; Sorsdahl, Katherine
Abstract : Objectives: To examine the feasibility and acceptability of integrating a 'designated' approach to community health worker (CHW)-delivered mental health counselling (where existing CHWs deliver counselling in addition to usual duties) and a 'dedicated' approach (where additional CHWs have the sole responsibility of delivering mental health counselling) into chronic disease care. Design: A feasibility test of a designated and dedicated approach to CHW-delivered counselling and qualitative interviews of CHWs delivering the counselling. Setting: Four primary healthcare clinics in the Western Cape, South Africa allocated to either a designated or dedicated approach and stratified by urban/rural status. Participants: Forty chronic disease patients (20 with HIV, 20 with diabetes) reporting hazardous alcohol use or depression. Interviews with seven CHWs. Intervention: Three sessions of structured mental health counselling. Main outcome measures: We assessed feasibility by examining the proportion of patients who were willing to be screened, met inclusion criteria, provided consent, completed counselling and were retained in the study. Acceptability of these delivery approaches was assessed through qualitative interviews of CHWs. Results: Regardless of approach, a fair proportion (67%) of eligible patients were willing to receive mental health counselling. Patients who screened positive for depression were more likely to be interested in counselling than those with hazardous alcohol only. Retention in counselling (85%) and the study (90%) was good and did not differ by approach. Both dedicated and designated CHWs viewed the counselling package as highly acceptable but requested additional training and support to facilitate implementation. Conclusions: Dedicated and designated approaches to CHW-delivered mental health counselling were matched in terms of their feasibility and acceptability. A comparative efficacy trial of these approaches is justified, with some adjustments to the training and implementation protocols to provide further support to CHWs.